A national cross-sectional study of the role of clinician specialty and facility complexity on glucocorticoid prescribing in Veterans - Beth I. Wallace; Shirley Cohen-Mekelburg; Tony Van; Rachel Lipson; Brooke Kenney; Chelsea Tatchin; Jessica Baker; Sameer D. Saini; Akbar K. Waljee (Communications Medicine)
Abstract Background: Glucocorticoids are used commonly despite their toxicity and availability of effective alternatives. Prior claims-based studies evaluating effect of clinician specialty on glucocorticoid prescribing do not examine how facility-level resources affect prescribing patterns. We aim to describe the effect of facility complexity and clinician specialty on oral glucocorticoid prescribing in the general population. Methods: This is a national cross-sectional study of Veterans prescribed oral glucocorticoids during 2021-2022. We defined glucocorticoid use as ≥1 outpatient pharmacy claim for oral glucocorticoids, and prolonged use as ≥30 days’ supply dispensed within 365 days. We defined complexity, rurality, and region using VHA operational metrics, and clinician specialty using NUCC taxonomy codes. We descriptively evaluated demographics, comorbidities, and healthcare utilization stratified by glucocorticoid use. We calculated the proportion of users and prolonged users at each facility, stratified by complexity, rurality, and region. We calculated the proportion of glucocorticoid prescriptions by clinician specialty. For three high-prescribing specialties, we calculated the facility-level proportion of glucocorticoid prescriptions by complexity designation. Results: Here we show that among 5,729,134 patients at 124 facilities, a mean of 12.1% (SD 3.5%) are glucocorticoid users; 2.1% (SD 0.5%) were prolonged users. Rates of use and prescribing vary substantially within and across facility complexity designations. Family practice represents 18.8% of glucocorticoid-prescribing clinicians but prescribes 26.3% of filled prescriptions. Family practice displays higher prescribing at lower-complexity sites. Conclusions: In this large national population, overall and prolonged glucocorticoid use are common and prescribing patterns vary by clinician type and complexity designation. Clinician-facing interventions to address knowledge gaps, incentivize non-glucocorticoid treatments, or facilitate specialty care access may reduce overuse among high-prescribing clinicians.